Power and Political Influence in Sports in Indonesia: A Literature Review - Hita, I Putu Agus Dharma; Pranata, Doni; Ariestika, Elsa (The Eastasouth Journal of Learning and Educations, 2024)
This research aims to analyze the power and political influence in sports in Indonesia. In this study, the author used a qualitative approach with data collection techniques through literature review. The results of the study showed that power and political influence greatly affect the development of sports in Indonesia, from the development of infrastructure, organization of sporting events, to the recruitment of athletes and coaches. Political influence also affects the integrity of sports, such as doping cases and cheating in competitions. In addition, power and political influence can have a negative impact on athletes and coaches, such as political intervention in technical decisions and the appointment of incompetent people as sports administrators. However, there have been several efforts made by the government and society to reduce the negative impact of power and political influence in sports, such as the formation of independent institutions and increasing awareness of sports integrity. Therefore, the conclusion of this study is that it is important to pay attention to the role and political influence in the development of sports in Indonesia, as well as taking appropriate steps to maintain integrity and minimize the negative impact of power and political influence in sports.